Pembelajaran Organisasi di Pondok Pesantren - Nurhadi Nurhadi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2013)
Pesantren as social religious organization plays important role in implementing the concept of education for all. Such concept accommodates the belief that every human being holds a right to be educated either formally or informally. The implication is through pesantren, somebody may learn to live a life well. Further, pesantren is responsible to develop its students to become intelligent and pious.